Telaah Sekolah Islam Terpadu Sebagai Pembaharuan Sistem Pendidikan Islam - Fernando, Yogi; Mariyanti , Nova; Aprison , Wedra (PT. ALHAFI BERKAH INDONESIA, 2023)
Integrated Islamic School is a formal educational institution which in its process combines general and religious education into one. Integrated Islamic Schools themselves are often said to be good and even a solution and renewal of the education system, especially Islamic education. With this in mind, this research tries to examine this statement using qualitative research where the main sources are journals that are deemed relevant as well as the author's personal experiences in integrated Islamic schools. And the results of the author's study show that it is true that integrated Islamic schools are good schools. However, it cannot be said to be 100% a solution and renewal for the education system, especially Islamic education, because integrated Islamic schools are like a double-edged sword and there are still things that need to be improved to achieve what is expected.